Investigating the effects of organic and inorganic forms of zinc , copper, and manganese on the productive trait and reproductive performance of broiler breeder hens - Mojaveriyan, SA; Gharahveysi, S; Hajipour, M (Journal of the Hellenic Veterinary Medical Society, 2025)
race minerals are essential for the bird's body, and are effective in its performance. The current study investigates the effects of organic and mineral forms of copper, zinc, and manganese on the production traits and reproductive performance of Ross 308 broiler breeders. So, 240 hens and 30 roosters were used. The research was conducted as a factorial experiment in the form of a completely randomized design. The factors included the A factor (2 levels of organic and inorganic forms) and the B factor (3 levels of zinc, copper, and manganese). The number of treatments, repeats, and pens were 6, 5, and 30, respectively. The data obtained from the reproductive and reproductive traits' measurements were analyzed with the LSmeans procedure by SAS statistical software. The effect of minerals, mineral forms, and their interaction was significant (p<0.05) on egg production, egg mass, egg weight, hatchable egg, fertility rate, hatchability egg, and chicken weight during weeks 36-33, 37-40, and the whole period. Organic zinc improved the studied traits and, in comparison to other factors, had the most significant effect on them.